Anti-factor Xa levels in obese patients receiving enoxaparin for treatment and prophylaxis indications - Tahaineh L; Edaily SM; Gharaibeh SF (Dove Medical Press, 2018)
Linda Tahaineh,1 Sahar M Edaily,1 Shadi F Gharaibeh2 1Department of Clinical Pharmacy, Faculty of Pharmacy, Jordan University of Science and Technology (JUST), Irbid, Jordan; 2Department of Pharmaceutical Sciences, Faculty of Pharmacy, Jerash University, Jerash, Jordan Objectives: To evaluate the degree of anticoagulation achieved with different enoxaparin dosing regimens used in obese and morbidly obese patients in a hospital setting in Jordan.Methods: All obese adult patients who were prescribed enoxaparin for various indications were invited to participate in the study. The anti-factor Xa (anti-Xa) level was checked once after 4–6 hours of the third or fourth dose of enoxaparin (at steady state). Patients were followed daily to evaluate drug efficacy and safety through their hospital course.Results: Enoxaparin daily dose used for prophylaxis indications ranged from 0.3 to 0.85 mg/kg and from 0.31 to 2.25 mg/kg in case of certain treatment indications. Most participants who received enoxaparin for treatment indications (76.9%) were on capping dosing regimens, which was <1 mg/kg twice daily. On the other hand, most patients (88.5%) who received enoxaparin for prophylaxis indications were on a fixed 40 mg/d dose. Among the 52 patients who completed the study, 19 patients (36.5%) had therapeutic anti-Xa levels. The results showed no statistically significant associations between regimens that were used and achieving therapeutic anti-Xa level (p>0.05). No bleeding events or thrombocytopenia were noticed, and there was one case of recurrent thrombosis.Conclusion: Enoxaparin dosing regimens that were used for obese patients varied based on prescribing physicians. Regardless of the regimen used, the majority of participants had nontherapeutic anti-Xa. Individualized dosing regimens based on anti-Xa levels are warranted for obese patients on enoxaparin. Keywords: anti-factor Xa, anticoagulation, enoxaparin, obesity